Medical and social features of patients with coronary artery disease and depression - Yu. V. Nagibina; M. I. Kubareva; D. S. Knyazeva (Кардиоваскулярная терапия и профилактика)
The article reflects the relevance of determining medical, social and psychological parameters that determine the quality of life (QOL) and depression risk in cardiovascular patients. It has been established that psychological disorders have a negative effect on patients with coronary artery disease (CAD) and are the predictors of health and QOL decline. That is why the clinical manifestations of CAD should be regarded as a result of the behavioral response of patients with depression. During analysis, it was concluded that depression effects not only on the health, but also on psychophysiological characteristics. In this regard, the main subject of study is the relationship of depression to the specific medical and social characteristics of a person. This justifies the need for timely diagnosis of depression and work with psychosocial factors in order to increase the effectiveness of treatment and prevention measures in CAD patients and improve their QOL.